Naturally acquired antibodies to the glutamate-rich protein are associated with protection against plasmodium falciparum malaria. - Dodoo, D.; Theisen, M.; Kurtzhals, J.A.L.; Akanmori, B.D.; Koram, K.A.; Jepsen, S.; Nkrumah, F.K.; Theander, T.G.; Hviid, L. (Journal of Infectious Diseases, 2000)
The development of effective malaria vaccines depends on the identification of targets of well-defined protective immune responses. Data and samples from a longitudinal study of a cohort of children from coastal Ghana were used to investigate the role of antibody responses to 3 regions of the Plasmodium falciparum glutamate-rich protein (GLURP). The data show that levels of the GLURP-specific IgG that occurs in the nonrepeat region of the antigen are significantly correlated with clinical protection from P. falciparum malaria, after correction for the confounding effect of age. Furthermore, levels of cytophilic antibodies were found to be of particular importance for protection, lending support to the hypothesis that antibody-dependent cellular inhibition is the important element in GLURP-specific protective immunity.